Prospects of chinese agriculture and the implications of the chinese economic miracle to asian agriculture - Huang, Jikun; Yang, Jun; Rozelle, Scott (2010)
The presentation provided an overview of China's agricultural performance in the past 30 years, the key driving forces of agricultural production and demand, and prospects of China's agriculture under alternative scenarios in 2020. The following questions were raised: "What have been major policies driving China's agricultural development in the past", "How will they change in the coming decades?" and "What are the implications of China's rapid economic growth to the rest of the world particular in Asia?".
China's economy in 2007 was 14.5 times that in 1978. In addition, despite lower growth rates in the agricultural sector, these growth rates have been about four to five times higher than population growth rates. The key driving forces of demand identified were population growth and changing lifestyle (e.g., income growth, urbanization/migration, and globalization). China's experience shows that institutional innovation, technology changes, market reform, infrastructure improvement, and off-farm employment are critical to agricultural development and food security.
China's rapid economic growth was assessed to neither threaten its national nor world food security if agricultural productivity were to exhibit moderate growth in the future.
The following conclusions were presented: 1) the rapid growth of China's economy will stimulate overall world economic growth and market opportunities for other countries in many land-intensive products (e.g., soybean, edible oil, feeds, sugar, cotton, tropical and sub-tropical products, and some livestock products such as (e.g. milk, beef, mutton, etc.) and 2) for many Asian countries, the gains may limit to only a few products such as tropical and sub-tropical crops and fruits. In many cases Asian countries may have to compete with China for export markets.
Keywords: Economic development -- Asia; Agricultural development; Food security